2018
DOI: 10.1111/1753-0407.12800
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort studies of birth weight and risk of obesity, diabetes, and hypertension in adulthood among the Chinese population

Abstract: The results suggest that LBW, an index of poor intrauterine nutrition, may affect health risks later in life in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
6
18
0
Order By: Relevance
“…However, there is also evidence that malnutrition in early life may increase susceptibility through multiple biological mechanisms . In our study we observed a significant association of low birth weight with the risk of obesity, diabetes, and hypertension, even after adjusting for most socioeconomic and lifestyle factors, such as education level, per capita income, smoking, alcohol consumption, and regular exercise, which mostly relieved our concern regarding the potential confounding effect of these factors.…”
supporting
confidence: 44%
See 1 more Smart Citation
“…However, there is also evidence that malnutrition in early life may increase susceptibility through multiple biological mechanisms . In our study we observed a significant association of low birth weight with the risk of obesity, diabetes, and hypertension, even after adjusting for most socioeconomic and lifestyle factors, such as education level, per capita income, smoking, alcohol consumption, and regular exercise, which mostly relieved our concern regarding the potential confounding effect of these factors.…”
supporting
confidence: 44%
“…We thank Dr Armando Arredondo for his response to our article evaluating the associations of birth weight with multiple anthropometric measurements and subsequent risk of type 2 diabetes mellitus and hypertension in Chinese adults …”
mentioning
confidence: 99%
“…Despite the evidence presented by Xia et al, the fact remains that arguments continue in favor and against the effects of birth weight on health risks throughout life. Several factors can act as confounders of the relationship between birth weight and the risk of diabetes and hypertension in later life, including smoking habits, diseases during pregnancy, the nutritional status of the mother, and socioeconomic status.…”
mentioning
confidence: 95%
“…In the best of cases, the evidence accumulated gives indications or suggests some kind of association between the variable birth weight and the development of chronic diseases, depending on the presence or absence of other variables. Such is the case of the study by Xia et al, which suggests that low birth weight can have consequences for health risks in adult life.…”
mentioning
confidence: 98%
See 1 more Smart Citation